A Weak C′ Box Renders U3 snoRNA Levels Dependent on hU3-55K Binding - Knox, Andrew Alexander (American Society for Microbiology, 2011)
The rate of ribosome biogenesis, which is downregulated in terminally differentiated cells and upregulated in most cancers, regulates the growth rate and is linked to the cell's proliferative potential. The U3 box C/D small nucleolar RNP (snoRNP) is an integral component of the small subunit (SSU) processome and is essential for 18S rRNA processing. We show that U3 snoRNP assembly, and therefore U3 snoRNA accumulation, is regulated through the U3-specific protein hU3-55K. Furthermore, we report that the levels of several SSU processome components, including the U3 snoRNA but not other box C/D snoRNAs, are specifically downregulated during human lung (CaCo-2) and colon (CaLu-3) epithelial cell differentiation. c-Myc is reported to play an integral role in regulating ribosome production by controlling the expression of many ribosome biogenesis factors. Our data, however, indicate that this regulation is not dependent on c-Myc since the level of this protein does not change during epithelial cell differentiation. In addition, depletion of c-Myc had only a mild affect on the levels of SSU processome proteins. CaCo-2 cells are colon adenocarcinoma epithelial cells that are believed to revert to their precancerous state during differentiation. This suggests a significant increase in the levels of specific SSU processome components during tumorogenesis.